Manalagi Apple Vinegar (Malus sylvestris Mill) as Anti Diabetic to Alloxan Induced Wistar White Male Rat - Purnomo, Valentina Verrel; Tjandra, Agustinus Sareh Arjono; Risma, Risma (Universitas Hang Tuah, 2019)
Apple vinegar is estimated to be able to cure diabetes. Vinegar is able to control the increase of glicemic index. Apple has antioxidant substance such as quercetin and chlorogenic acid. Manalagi apple could be found easily in Indonesia. This research aims to reveal the effect of Manalagi apple vinegar (Malus sylvestris Mill) towards blood glucose level of alloxan induced Wistar white male rats (Rattus norvegicus). This research is experimental laboratory using Experimental methods. The samples are 30 white rats divided into three groups for 31 days, 1) group which only given standard diet; 2) group that induced by 120mg/dL alloxan; 3) group that induced by 120mg/dL alloxan and Manalagi apple vinegar 0.27ml/100gram weight for 14 days. The measurement of blood serum glucose level is done on day twenty four using homogenous colorimetric enzymatic test method for all groups. Blood glucose average in group with only given standard diet as negative control group (182.33 mg/dL), group which induced by 120mg/dL alloxan as positive control group (205.2 mg/dL), group which induced by 120mg/dL alloxan and Manalagi apple vinegar as treatment group (212.25 mg/dL). The result of One-Way Anova significance is 0.229. The conclusion of this research is that Manalagi apple vinegar treatment doesn’t able to decrease the blood glucose level of white Wistar male rats significantly. Keywords : Malus sylvestris Mill, Blood glucose, Alloxan.